1997
DOI: 10.1002/(sici)1098-1004(1997)10:3<217::aid-humu7>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Novel point mutations in the dystrophin gene

Abstract: Duchenne (DMD) and Becker (BMD) type muscular dystrophies are allelic X-linked recessive disorders caused by mutations in the gene encoding dystrophin. About 65% of the cases are caused by deletions, while 5-10% are duplications. The remaining 30% of affected individuals may have smaller mutations (point mutations or small deletions/insertions) which cannot be identified by current diagnostic screening strategies. In order to look for pathogenic small mutations in the dystrophin gene, we have screened the 18 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…4A,C). By comparison, a nonsense mutation in exon 4 of human DMD causes DMD, indicating that this exon is essential in human muscle (Sitnik et al, 1997). The N-terminal location of this mutation indicates that other shorter isoforms produced from downstream alternative first exons should be expressed normally in other tissues, as confirmed by immunohistochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A,C). By comparison, a nonsense mutation in exon 4 of human DMD causes DMD, indicating that this exon is essential in human muscle (Sitnik et al, 1997). The N-terminal location of this mutation indicates that other shorter isoforms produced from downstream alternative first exons should be expressed normally in other tissues, as confirmed by immunohistochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the mutations in dystrophin that trigger muscular dystrophy [listed in the Leiden MD mutation database (http:// www.dmd.nl/) and Human Gene Mutation Database (http:// www.hgmd.cf.ac.uk/)], a major fraction of missense mutations (>50%) occurs in N-ABD (16)(17)(18). We probed the effect of four mutations on the structure and stability of N-ABD: L54R, which triggers DMD; and A168D, A171P, and Y231N, which trigger BMD (16,(18)(19)(20).…”
mentioning
confidence: 99%
“…About 30-35% cases of D/BMD are assumed to result from microdeletions, microinsertions or substitutions of one or more nucleotide(s). Several independent studies have reported small mutations in the dystrophin gene (Kiliman et al, 1992;Nigro et al, 1992Nigro et al, , 1994Roberts et al, 1992;Tuffery et al, 1993Tuffery et al, , 1995Tuffery et al, , 1996Kneppers et al, 1995;Sitnik et al, 1997;Eranslan et al, 1999;Wibawa et al, 2000). These are randomly distributed throughout the dystrophin gene (http://www.dmd.nl).…”
Section: Introductionmentioning
confidence: 70%
“…They In the present study, sequencing showed a nucleotide substitution of G to T in the intronic region (2201-37G/ T) in two patients (MD-138 and MD-70) and a nucleotide substitution in the exon 17 (C2268T) in one (MD-28). The observed intronic nucleotide change in the dystrophin gene has been reported earlier by many independent investigators (Kiliman et al, 1992;Tuffery et al, 1992;Nigro et al, 1994;Prior et al, 1995;Sitnik et al, 1997). They have observed this not only in D/ BMD patients but also in normal individuals, thereby constituting a rare polymorphism.…”
Section: Discussionmentioning
confidence: 99%